Effects of zeolite frameworks and hierarchical structures on catalytic bioethanol dehydration: In-situ DRIFTS and DFT studies - Iadrat, Ploychanok; Yomthong, Krissanapat; Rodaum, Chadatip; Pornsetmetakul, Peerapol; Thivasasith, Anawat; Prasertsab, Anittha; Fan, Xiaolei; Sooknoi, Tawan; Wattanakit, Chularat (My University, 2023)
Herein, the combined in-situ diffuse reflectance infrared Fourier transform spectroscopy and density functional theory studies were employed to investigate the effects of different zeolite frameworks and hierarchical structures on catalytic bioethanol dehydration. The findings reveal that different zeolite frameworks enable the formation of distinct intermediates, hence promoting different mechanistic pathways. Interestingly, the FER is highly selective to ethylene and inhibits the formation of by-products thanks to the confined porous structure of the FER. Although the pristine small pore FER often suffers from fast catalyst deactivation, the incorporation of hierarchical structures in the FER framework can mitigate this significantly. Accordingly, the catalytic stability of the hierarchical FER was improved remarkably with a high ethylene yield (∼95%), whereas the pristine FER suffers from fast deactivation. Additionally, coke formation over the hierarchical FER catalyst was also reduced significantly compared to that of the pristine FER. Importantly, the in-situ DRIFTS studies reveal that the different reaction pathways over hierarchical and commercial FER have been observed in which the hierarchical one promotes the monomeric pathway due to the facile desorption of corresponding products and intermediates, whilst the pristine one promotes bioethanol conversion via both pathways of monomeric and dimeric pathways to produce ethylene and diethyl ether, respectively.
Keywords: Bioethanol dehydration; DFT calculations; Hierarchical zeolites; In-situ DRIFTS studies; Zeolite frameworks